Variability in Prices for Erectile Dysfunction Medications—Are All Pharmacies the Same?. Issue 12 (1st December 2018) - Mishra, Kirtishri; Bukavina, Laura; Mahran, Amr; Bobrow, Aidan; Buzzy, Christina A.; Jain, Nishant; Gnessin, Ehud; Loeb, Aram; Ponsky, Lee E.
Abstract: Background: Variability in prices of medications is a well-known phenomenon; however, this variability has not been quantified in the realm of erectile dysfunction (ED) medications. ED medications are ideal for this quantification, because they are often not covered by insurances; therefore, the cost is the most direct reflection of price variability among pharmacies as they affect the patients. Aim: To evaluate the variability in cash prices for phosphodiesterase type 5 inhibitors (PDEIs) for ED. We also evaluated whether certain types of pharmacies consistently offer better pricing than others, and whether there was any correlation with demographic factors. Methods: 331 pharmacies were contacted within a 25-mile radius of our institution to obtain the cash price for 4 commonly used ED medications with prespecified doses. After exclusion, 323 pharmacies were categorized as chain, independent, wholesale, or hospital-associated. Cash prices for the specified medications were evaluated. In addition, we identified demographic and socioeconomic factors to determine if these had an impact on median drug pricing within each zip code. Main Outcome Measure: The main outcome was the cost for patients to fill each prescription. Results: Independent pharmacies provided the lowest cost for 3 of 4 of the PDEIs. The largest price difference for 10 tablets of 100 mg sildenafil between all pharmacies was 38, 000%. The median cost difference between independent pharmacies and chain pharmacies for sildenafil was >900%, and >1, 100% for independent pharmacies vs hospital-associated pharmacies. Demographic and socioeconomic factors had no impact on the cost. Clinical Implications: Our goal is to promote patient counseling among practitioners and to empower patients to shop for the best prices for their medications. Strength and Limitations: A strength of the study is the large cohort that was surveyed; however, a weakness is that the large majority of the cohort was comprised of chain pharmacies. Mail pharmacies could not be evaluated as they required a valid prescription before offering prices. Conclusion: The drastic differences in cash prices for the PDEIs give us an insight into the variability and cost-inflation of medications in the United States. These patterns hold true for other essential medications as well, and improved transparency will allow patients to make informed decisions when choosing where to purchase their medications. It may also encourage certain pharmacies to provide medications at more affordable prices.